Jian-Pi-Bu-Xue-Formula Alleviates Cyclophosphamide-Induced Myelosuppression via Up-Regulating NRF2/HO1/NQO1 Signaling - Huang, Qiuju; Feng, Lizhi; Li, Hang; Zheng, Liang; Qi, Xiaoxiao; Wang, Ying; Feng, Qian; Liu, Zhongqiu; Liu, Xiaohong; Lu, Linlin (Frontiers in Pharmacology, 2020)
Jian-pi-bu-xue-formula (JPBXF), a TCM formula composed of twelve Chinese medicinal herbs, has been used in clinic to ease patients’ state of weakness and fatigue especially after receiving anti-tumor chemotherapy in China. The lack of the phytochemical characterization, detail therapeutic evaluation and mechanism of JPBXF remains the main limitation for its spreading. In this study, we systematically evaluated the effectiveness and underline mechanism of JPBXF on cyclophosphamide (CTX)-induced myelosuppression and identified the main constituents of JPBXF aqueous extract. JPBXF treatments reversed CTX-induced myelosuppression through increasing the number of haematopoietic stem cells (HSCs) and expression of C-kit in bone marrow cells. Simultaneously, JPBXF treatments alleviated CTX-induced blood cells reduction by increasing numbers of RBCs and WBCs and levels of GM-CSF, TPO and EPO in plasma. JPBXF treatments reduced CTX-induced immunosuppression by increasing expressions of CD3, CD4, and CD8a in PBMCs, and recovering structure damages of thymus and spleen. Moreover, JPBXF notably increased the expression of NRF2 compared with CTX group, and subsequently up-regulated HO1 and NQO1 both in mRNA and protein levels. In addition, eighteen compounds were recognized from JPBXF aqueous extract and the potential targets of the identified compounds were predicted. Overall, JPBXF can greatly reverse CTX-induced myelosuppression in C57BL/6 mice, especially in improving the blood and immune function through activating NRF2/HO1/NQO1 signaling pathway, which provides a reliable reference for JPBXF application in clinical. By recognizing eighteen compounds in JPBXF aqueous extract and predicting the underline mechanisms of the identified compounds, our study would provide theoretical guidance for further research of JPBXF.